2017
DOI: 10.1016/j.jhevol.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of rotational inertia of primate mandibles

Abstract: The relative importance of pendulum mechanics and muscle mechanics in chewing dynamics has implications for understanding the optimality criteria driving the evolution of primate feeding systems. The Spring Model (Ross et al., 2009b), which modeled the primate chewing system as a forced mass-spring system, predicted that chew cycle time would increase faster than was actually observed. We hypothesized that if mandibular momentum plays an important role in chewing dynamics, more accurate estimates of the rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
(85 reference statements)
2
13
0
Order By: Relevance
“…We report the results of the phylogenetic RMA with five parameters: the estimate of the scaling exponent (b); the squared correlation coefficient (R 2 ); the p-value for devation from isometry comparing exponents using an F-test (p); Pagel's λ, a measure of how well the phylogeny explains the data (λ=1 suggests the evolution of the observed traits follows a Brownian motion model with variance proportional to divergence times, whereas λ=0 suggests phylogenetic independence); and the log-likelihood (L) [42] in Table 3. We considered also using phylogenetic generalized least squares (PGLS) analysis, but as prior studies have found negligible differences between phylogenetic RMA and PGLS results or conclusions [43,44], we opted to apply only phylogenetic RMA to our data, thereby retaining a closer methodological equivalence to our standard scaling analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We report the results of the phylogenetic RMA with five parameters: the estimate of the scaling exponent (b); the squared correlation coefficient (R 2 ); the p-value for devation from isometry comparing exponents using an F-test (p); Pagel's λ, a measure of how well the phylogeny explains the data (λ=1 suggests the evolution of the observed traits follows a Brownian motion model with variance proportional to divergence times, whereas λ=0 suggests phylogenetic independence); and the log-likelihood (L) [42] in Table 3. We considered also using phylogenetic generalized least squares (PGLS) analysis, but as prior studies have found negligible differences between phylogenetic RMA and PGLS results or conclusions [43,44], we opted to apply only phylogenetic RMA to our data, thereby retaining a closer methodological equivalence to our standard scaling analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Because most chewing occurs on posterior teeth, where proximity to the jaw joint increases both mechanical advantage and bite force, the force-gape trade-off imposes particularly strict limits on the size of the bolus that can be fractured efficiently. Chewing systems, moreover, operate at relatively consistent speedsthere is no fast chewing speed analogous to running or galloping, and selection for improved feeding performance does not appear to result in faster chewing (Ross and Iriarte-Diaz, 2014;Ross et al, 2017). In sum, tetrapod chewing involves precise application of force over a narrow, controlled and predictable range of displacements, the principal aim of chewing being to fracture the substrate, the size and mechanical properties of which are controlled at ingestion and further reduced and homogenized, respectively, by the chewing process.…”
Section: Cyclic Behaviors: Chewing Versus Walking and Runningmentioning
confidence: 99%
“…For example, diversity in feeding-system morphology has been related to variation in feeding behavior and diet in a wide range of vertebrates, including fish, birds, lizards and mammals (Olsen, 2017;Reilly and McBrayer, 2007;Westneat, 2004), and diversity in locomotor morphology has been linked to variation in locomotor mode, ecology, substrate preference and overall habitat (Fabre et al, 2017;Garland and Losos, 1994;Higham, 2007;. In contrast with the many studies examining diversity within feeding and locomotor systems, studies that explicitly compare the two systems are much less common, despite the insight they provide into general principles of musculoskeletal design (Ahn et al, 2018;English, 1985;Higham, 2007;Ross et al, 2017). Here, we relate variation in joint angular excursions during cyclic behaviorschewing, walking and runningto variation in the functional optimality criteria and mechanical constraints governing the evolution of feeding and locomotor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Body size introduces another level of complexity to musculoskeletal functional morphology due to the negative allometry of force production to body mass (e.g., Biewener, 1989;Biewener, 1990). The effects of scaling extend to not only the duration of vertebrate locomotor and feeding cycles-and therefore potentially to the relative velocity of muscle fibers-but also the timing of muscle activation in appendages large enough to utilize momentum for movement (Pennycuick, 1975;Pontzer, 2007;Hooper et al, 2009;Ross et al, 2009;Gintof et al, 2010;Hooper, 2012;Ross et al, 2017). Cycle duration, musculoskeletal design, and the spring-like properties of muscle-tendon units may also function to reduce energy expenditure and fatigue (Taylor, 1985;Cavagna et al, 1997;Marsh et al, 2004;Raichlen, 2004;Modica and Kram, 2005;Hunter and Smith, 2007;Pontzer, 2007;de Ruiter et al, 2013;Hoffman, 2013, 2015), and some organisms may be optimized for submaximal activations and endurance at longer fiber lengths rather than maximal activations and power at "optimal" fiber lengths.…”
Section: Activity Patterns and Physiologymentioning
confidence: 99%
“… Throughout this article, we define musculoskeletal design as the relationship among musculoskeletal morphology, physiology, and biomechanical performance—in short, form:function relationships (Ross et al, ).…”
mentioning
confidence: 99%